The Harmonization of Judicial Status: Urgency of the Draft Law on the Magistracy in Affirming Judges as State Officials and Its Impact on Judicial Human Resource Management - Jesica, Kenny (Ultimate Journal of Legal Studies, 2024)
The affirmation of judges status as state officials in the Draft Law of the Magistracy (RUU Jabatan Hakim) constitutes an urgent constitutional measure to strengthen the independence of judicial power in Indonesia. Although Law No. 48 of 2009 has explicitly recognized judges as state officials, in practice this status continues to overlap with the civil service regime. This dualism has created structural problems that undermine judicial independence, as judges remain bound by career patterns, salary systems, and disciplinary mechanisms under executive control. This normative legal research aims to analyze the urgency of affirming judges pure status as state officials and to formulate the concept of a complete separation from the Civil Service system. The findings indicate that recognizing judges as state officials would provide stronger legal protection, ensure autonomy in appointment and promotion, and establish a sui generis career system based on competence and integrity. The Draft Law on the Judiciary is expected to create an independent judicial personnel system encompassing proportional regulations on salaries, allowances, and pensions in line with the dignity of the judicial office. However, judicial independence must be balanced with accountability through transparent ethical and technical oversight by the Supreme Court and the Judicial Commission. Therefore, the formulation of the Draft Law on the Judiciary represents not merely an administrative reform, but a fundamental effort to uphold the independence of judicial power as mandated by Article 24 of the 1945 Constitution, and to reinforce public trust in the judiciary as the ultimate guardian of justice.